Literasi digital, etika bisnis Islam, dan inovasi produk sebagai determinan keputusan pembelian konsumen pada marketplace Shopee di Kecamatan Banyuanyar - Daniel M. Rafli Agustias; Maula Nasrifah; Ahmad Fajri (Nur Science Institute, 2026)
This study examines the effects of digital literacy, Islamic business ethics, and product innovation on consumers’ purchasing decisions on the Shopee marketplace in Banyuanyar District. The study was conducted in response to the limited research integrating digital literacy and Islamic business ethics within the context of marketplace use in semi-rural areas. A quantitative approach with an associative research design was employed. The sample consisted of 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression. The results indicate that digital literacy, Islamic business ethics, and product innovation each have a positive and significant effect on purchasing decisions. Simultaneously, all three independent variables significantly influence consumers’ purchasing decisions. These findings imply that marketplace sellers should improve the quality of digital information, apply Islamic business ethics principles, and develop product innovations that respond to consumer needs. In addition, marketplace providers and local governments should strengthen digital literacy programs and business assistance initiatives to help consumers and business owners in semi-rural areas use digital marketplaces more effectively, ethically, and sustainably.